Burden of influenza during the first year of life - Mattila Janna‐Maija; Thomas Emilia; Lehtinen Pasi; Vuorinen Tytti; Waris Matti; Heikkinen Terho (Wiley, 2022)
Background
Every year, influenza viruses infect millions of children and cause an enormous burden of disease. Young children are at the highest risk for influenza-attributable hospitalizations. Nevertheless, most young children are treated as outpatients, and limited data are available on the burden of influenza in these children.
Methods
We carried out a prospective cohort study and followed 431 infants born in June-August 2017 for 10 months from September 1, 2017, to June 30, 2018. The parents filled out daily symptom diaries and were instructed to bring their child for clinical examination at our study clinic each time the child had fever or any signs or symptoms of respiratory tract infection. During each visit, we obtained nasopharyngeal swab specimens for determination of the viral etiology of the illness.
Results
A total of 55 episodes of laboratory-confirmed influenza were diagnosed among the 408 actively participating children, which corresponds to an annual incidence rate of 135/1000 children (95% Cl, 102-175). Excluding five children with double viral infection, acute otitis media developed as a complication of influenza in 23 (46%) children. One (2%) child with influenza was hospitalized because of febrile convulsion. The effectiveness of influenza vaccination was 48% (95% CI, -29%-80%).
Conclusions
The burden of influenza during the first year of life is heavy in the outpatient setting where most infants with influenza are managed. Effective strategies for the prevention of influenza particularly in infants under 6 months of age are needed to diminish the burden of disease in this age group.